Housing and Neoliberalism A Case of Affordable Public Housing in Pakistan - Abdul Rehman,; Peter Aning Tedong,; Melasutra Md. Dali, (2024)
Affordable public housing has garnered much scholarly interest, which led to extensive research in the last two decades. Despite its effectiveness in providing affordable housing on a global scale, affordable housing in Pakistan is scarce with a shortage of approximately 10 million units. This qualitative study used a political economy theory of neoliberalism to examine affordable public housing development in Lahore, Pakistan and a case study design to explore the complexities underpinning affordable public housing production. Notably, 22 in-depth interviews were conducted with key stakeholders in the public housing delivery process. The qualitative data were thematically analysed to identify salient themes on governance and regulatory challenges. Based on in-depth interviews with key government officers and policy document analysis, specific barriers to the urban governance system in developing affordable public housing were identified in Lahore. High urbanisation rates and land prices, inflation, the absence of low-income quota, lack of coordination, overlapping jurisdictions among government departments, and lack of political will primarily deter stakeholders from developing affordable public housing. For example, the various institutions from federal, provincial, and local governments in Lahore that work concurrently to provide affordable housing result in an overlapping of power between agencies. The current practice of providing individuals with open land plots to construct lowcost houses proved ineffective following its contribution to horizontal expansion and land price speculation. As such, the Pakistani government encounters challenges in providing affordable public housing for low-income earners. Following the neoliberal ideology, the Pakistani government ceased to engage in housing development and heavily relied on the private sector instead. This situation, which limited low-income earners’ options in formal housing, compelled them to live in informal settlements. Specific recommendations (adopting affordable housing policies at the provincial level, providing built strata housing rather than land-based, open-plot ones, and a low-income quota for every public housing scheme) were made to improve the current regulatory framework and affordable public housing delivery processes in Lahore, Pakistan.